Stress-Related Gene Expression Reflects Morphophysiological Responses to Water Deficit . Issue 3 (18th May 2017) - Rymaszewski, Wojciech; Vile, Denis; Bediee, Alexis; Dauzat, Myriam; Luchaire, Nathalie; Kamrowska, Dominika; Granier, Christine; Hennig, Jacek
Abstract : Morphophysiological acclimation to long-term water deficit is linked to the transcriptional response and reflected by gene expression levels measured in intact Arabidopsis. Abstract: Acclimation to water deficit (WD ) enables plants to maintain growth under unfavorable environmental conditions, although the mechanisms are not completely understood. In this study, the natural variation of long-term acclimation to moderate and severe soil WD was investigated in 18 Arabidopsis ( Arabidopsis thaliana ) accessions using PHENOPSIS, an automated phenotyping platform. Soil water content was adjusted at an early stage of plant development and maintained at a constant level until reproductive age was achieved. The accessions were selected based on the expression levels of ANNEXIN1, a drought-related marker. Severe WD conditions had a greater effect on most of the measured morphophysiological traits than moderate WD conditions. Multivariate analyses indicated that trait responses associated with plant size and water management drove most of the variation. Accessions with similar responses at these two levels were grouped in clusters that displayed different response strategies to WD . The expression levels of selected stress-response genes revealed large natural variation under WD conditions. Responses of morphophysiological traits, such as projected rosette area, transpiration rate, and rosette water content, were correlated with changes in the expression of stress-related genes, such as NINE-CIS-EPOXYCAROTENOID DIOXYGENASE3 and N-MYC DOWNREGULATED-LIKE1 ( NDL1 ), in response to WD . Interestingly, the morphophysiological acclimation response to WD also was reflected in the gene expression levels (most notably those of NDL1, CHALCONE SYNTHASE, and MYB DOMAIN PROTEIN44 ) in plants cultivated under well-watered conditions. Our results may lead to the development of biomarkers and predictors of plant morphophysiological responses based on gene expression patterns.